Dietary choline, but not L-carnitine, increases circulating lipid and lipoprotein concentrations, without affecting body composition, energy expenditure or respiratory quotient in lean and obese male cats during weight maintenance - Rankovic, Alexandra; Verton-Shaw, Shoshana; Shoveller, Anna K.; Bakovic, Marica; Kirby, Gordon; Verbrugghe, Adronie (Frontiers in Veterinary Science, 2023)
Due to the involvement in one-carbon metabolism and lipid mobilization, choline and L-carnitine supplementation have been recommended to minimize hepatic lipid accumulation and support fat oxidation, respectively. This study investigated the lipotropic benefits of choline or L-carnitine supplementation in lean and obese cats maintaining body weight (BW). Lean (n=9; body condition score [BCS]:4-5/9) and obese (n=9;BCS:8-9/9) adult male neutered colony cats were used in a replicated 3 x 3 complete Latin square design. Treatments included choline (378 mg/kg BW 0.67 ), L-carnitine (200 mg/kg BW) and control (no supplement). Treatments were supplemented to the food for 6 weeks each, with a 2-week washout between treatments. Cats were fed once daily to maintenance energy requirements, and BW and BCS were assessed weekly. Fasted blood collection, indirect calorimetry, and dual-energy X-ray absorptiometry occurred at the end of each treatment period. Serum was analyzed for cholesterol (CHOL), high-density lipoprotein CHOL (HDL-C), triglycerides (TAG), non-esterified fatty acids (NEFA), glucose, creatinine (CREAT), urea, alkaline phosphatase (ALP) and alanine aminotransferase (ALT). Very low-density lipoprotein CHOL (VLDL) and low-density lipoprotein CHOL (LDL-C) were calculated. Data were analyzed using proc GLIMMIX, with group and period as random effects, and treatment, body condition, and their interaction as fixed effects, followed by a Tukey's post-hoc test when significance occurred. Cats supplemented choline had lower food intake (P=0.025). Treatment did not change BW, BCS and body composition (P>0.05). Obese cats had greater ALP, TAG, and VLDL, and lower HDL-C compared to lean cats (P<0.05). Choline resulted in greater CHOL, HDL-C, LDL-C and ALT (P<0.05). L-carnitine resulted in lower CREAT (P=0.010). Following the post-hoc test, differences between treatment means were not present for ALP (P=0.042). No differences were found for glucose, urea or NEFA (P>0.05). Obese cats had a lower fed respiratory quotient (RQ), regardless of treatment (P=0.045). Treatment did not affect fed or fasted RQ and energy expenditure (P>0.05). Choline appeared to increase circulating lipid and lipoprotein concentrations regardless of body condition, likely through enhanced lipid mobilization and hepatic elimination. Neither dietary choline or L-carnitine altered body composition or energy metabolism in the lean or obese cats, as compared to control.